Carbon fiber composite material suitable for reinforcing communication tower and preparation method of carbon fiber composite material
By grafting dichlorodiphenylsulfoxide with nano-microcrystalline cellulose in the same direction, the problem of poor shearing ability of carbon fiber composite materials in the middle layer reinforcement of communication towers is solved, and the high strength and bending resistance of the material are achieved, which is suitable for the reinforcement of communication towers and improves structural stability and safety.
Patent Information
- Application Number
- CN202510229192.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When used for communication tower reinforcement, existing carbon fiber composite materials have poor interlayer shear capabilities, making it difficult to take into account the high strength in the fiber direction and the strength in the vertical fiber direction, lack of wear resistance, and are relatively expensive.
By grafting dichlorodiphenylsulfoxide nanocrystalline cellulose in the same direction, and using specific treatment methods, the interlayer shear strength, lateral tensile strength and bending resistance of carbon fiber composite materials are improved.
The excellent interlayer shear performance, lateral tensile performance, flexural modulus and flexural strength of carbon fiber composite materials are achieved, ensuring strength while reducing weight, reducing manufacturing costs, and suitable for reinforcement of communication towers, improving structural stability and safety.
Smart Images

Figure CS2PZZ1BDFWTK783ZOBBIT7ZPKNO9NQRDB7BLYYP
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a carbon fiber composite material suitable for strengthening a communication tower and a preparation method thereof. Background Art
[0002] With the rapid development of information technology, the coverage of wireless communication networks is constantly expanding, and the requirements for communication infrastructure are becoming higher and higher. As a key component of wireless communication networks, communication towers not only undertake the task of signal transmission, but also need to have sufficient structural strength to withstand the influence of the natural environment, such as wind and earthquakes. Therefore, the structural safety and stability of communication towers have become one of the important factors to ensure the quality of communication.
[0003] Traditional communication towers are mostly constructed of steel. Although steel has good strength and toughness, it is prone to corrosion, aging and other problems during long-term use, especially under harsh natural conditions, which in turn affects the safety and service life of the communication towers.
[0004] In recent years, carbon fiber composites have been widely used in many fields due to their advantages such as light weight, high strength and corrosion resistance. In particular, in terms of structural reinforcement, carbon fiber composites have shown advantages that are difficult to match with traditional materials. However, when used in communication tower reinforcement, existing carbon fiber composites still have some shortcomings: (1) The interlaminar shear capacity of conventional carbon fiber composites is poor, especially the carbon fiber composite laminates prepared by unidirectional prepreg lamination; (2) The carbon fiber composite panels used for communication tower reinforcement are all laid in the same direction, but in actual use conditions, they need to have extremely high strength in the fiber direction and high strength in the perpendicular fiber direction, and these two points are difficult to meet at the same time; (3) The wear resistance is poor. The carbon fiber layer required for communication tower reinforcement is usually bonded to the outer surface and directly contacts the external environment. For areas with strong wind and sand, sand erosion usually occurs on the surface after three years of reinforcement, and more pits appear on the surface, reducing the reinforcement effect of the carbon fiber bonding layer; (4) Carbon fiber composite panels usually modified by carbon nanotubes can improve the interlaminar shear performance, but they are expensive.
[0005] The inventors found that nanocrystalline cellulose (CNCs) has a large specific surface area, which provides an ideal interface for load transfer between carbon fiber layers and can improve the interlaminar shear strength of carbon fiber composites. Only by making the nanocrystalline cellulose in the same direction can the transverse tensile strength and bending resistance of carbon fiber composites be improved. To achieve this goal, the inventors tried to explore how to solve the problem of making the nanocrystalline cellulose in the same direction, so as to improve the transverse tensile strength of carbon fiber composites, which is then suitable for reinforcing communication towers.
[0006] In order to achieve the above-mentioned nano-microcrystalline cellulose being in the same direction, the inventors found that the above-mentioned purpose can be achieved by grafting dichlorodiphenyl sulfoxide onto nano-microcrystalline cellulose and adopting a specific treatment method. Summary of the invention
[0007] The invention aims to solve the problem that nano-microcrystalline cellulose is difficult to be in the same direction, the transverse tensile strength and bending resistance of carbon fiber composite materials cannot be improved, and the interlayer shear capacity is poor.
[0008] In order to achieve the above object, the first aspect of the present invention provides a carbon fiber composite material suitable for strengthening a communication tower, wherein the preparation method of the carbon fiber composite material comprises: S1: adding potassium hydroxide and nano-microcrystalline cellulose into ethanol, performing a first stirring, a first ultrasound, a first reaction, and a first post-treatment to obtain hydroxy nano-microcrystalline cellulose; S2: adding the hydroxy nano-microcrystalline cellulose to dimethylformamide, performing a second stirring, a second ultrasonication, dropping acetoxypropyltrimethoxysilane, performing a second reaction, and a second post-treatment to obtain amino nano-microcrystalline cellulose; S3: adding maleic anhydride-dichlorodiphenyl sulfoxide to toluene for swelling, adding the amino nano-microcrystalline cellulose, stirring for the third time, ultrasonicating for the third time, carrying out a third reaction at 120-125° C. for 2-2.5 hours, adding triethylamine at 75-85° C. for the fourth reaction for 24-25 hours, and carrying out a third post-treatment to obtain dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose; S4: Mix water and dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose for 15-30 minutes to obtain a dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension, spray the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension with a mass concentration of 0.1-0.5wt% on the upper surface of the prepreg, perform a fourth ultrasonication, dry, and perform a random inspection, and stack the prepregs with uniform distribution of dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose that have passed the random inspection to form N layers, wherein 2≤N≤3000, and the upper surface of each layer of the prepreg sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose is oriented in the same direction, and the uppermost layer is a prepreg not sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose, which is immersed in epoxy resin for 0.5-1h, with a vacuum degree of 0.01-0.1MPa, and cured to obtain a carbon fiber composite material.
[0009] A second aspect of the present invention provides a method for preparing the above-mentioned carbon fiber composite material suitable for strengthening a communication tower, wherein the preparation method comprises: S1: adding potassium hydroxide and nano-microcrystalline cellulose into ethanol, performing a first stirring, a first ultrasound, a first reaction, and a first post-treatment to obtain hydroxy nano-microcrystalline cellulose; S2: adding the hydroxy nano-microcrystalline cellulose to dimethylformamide, performing a second stirring, a second ultrasonication, dropping acetoxypropyltrimethoxysilane, performing a second reaction, and a second post-treatment to obtain amino nano-microcrystalline cellulose; S3: adding maleic anhydride-dichlorodiphenyl sulfoxide to toluene for swelling, adding the amino nano-microcrystalline cellulose, stirring for the third time, ultrasonicating for the third time, carrying out a third reaction at 120-125° C. for 2-2.5 hours, adding triethylamine at 75-85° C. for the fourth reaction for 24-25 hours, and carrying out a third post-treatment to obtain dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose; S4: Mix water and dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose for 15-30 minutes to obtain a dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension, spray the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension with a mass concentration of 0.1-0.5wt% on the upper surface of the prepreg, perform a fourth ultrasonication, dry, and perform a random inspection, and stack the prepregs with uniform distribution of dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose that have passed the random inspection to form N layers, wherein 2≤N≤3000, and the upper surface of each layer of the prepreg sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose is oriented in the same direction, and the uppermost layer is a prepreg not sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose, which is immersed in epoxy resin for 0.5-1h, with a vacuum degree of 0.01-0.1MPa, and cured to obtain a carbon fiber composite material.
[0010] A third aspect of the present invention provides a carbon fiber composite material obtained by the above preparation method.
[0011] A fourth aspect of the present invention provides application of the carbon fiber composite material described in the first aspect or the carbon fiber composite material described in the third aspect in reinforcing a communication tower structure.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The carbon fiber composite material provided by the present invention uses grafted dichlorodiphenyl sulfoxide and adopts a specific processing method to make the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose in the same direction, has excellent interlaminar shear performance, transverse tensile performance, bending modulus and bending strength, ensures strength while reducing weight, has low manufacturing cost, is used for reinforcing communication towers, can effectively improve the structural stability and safety of communication towers, extend their service life, and meet the needs of modern communication infrastructure construction.
[0013] The carbon fiber composite material prepared by the preparation method provided by the present invention has excellent interlaminar shear strength and transverse tensile performance, has a simple process, is green and environmentally friendly, has high production efficiency, and is low in cost, and can realize large-scale industrial production and application. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] CNCs have a large specific surface area and are widely used in the field of materials. Carbon fiber composites have poor interlaminar shear performance, and it is difficult to have extremely high strength in both the fiber direction and the perpendicular fiber direction. They have insufficient wear resistance and are expensive. This provides an ideal interface for interlaminar load transfer of carbon fibers. When used in carbon fiber composites, they can improve the interlaminar shear strength of carbon fiber composites. Carbon fiber composites with only excellent interlaminar shear strength still need excellent transverse tensile strength and bending resistance.
[0016] However, the inventors have found that if the fiber directions of the carbon fiber composite material are in the same direction, it can have both interlaminar shear strength, transverse tensile strength and bending resistance. The fiber directions are in the same direction means that the main chain structure of the nano-microcrystalline cellulose is in the same direction and is perpendicular to the single carbon fiber direction.
[0017] To achieve this goal, the inventors tried to explore how to make the fibers of carbon fiber composite materials in the same direction, so that the interlayer shear strength, transverse tensile strength and bending resistance of the carbon fiber composite materials can be improved, so that they can be used to reinforce communication towers, which can effectively improve the structural stability and safety of communication towers, extend their service life, and meet the needs of modern communication infrastructure construction.
[0018] To this end, a first aspect of the present invention provides a carbon fiber composite material suitable for strengthening a communication tower, wherein a method for preparing the carbon fiber composite material comprises: S1: adding potassium hydroxide and nano-microcrystalline cellulose into ethanol, performing a first stirring, a first ultrasound, a first reaction, and a first post-treatment to obtain hydroxy nano-microcrystalline cellulose; S2: adding the hydroxy nano-microcrystalline cellulose to dimethylformamide, performing a second stirring, a second ultrasonication, dropping acetoxypropyltrimethoxysilane, performing a second reaction, and a second post-treatment to obtain amino nano-microcrystalline cellulose; S3: adding maleic anhydride-dichlorodiphenyl sulfoxide to toluene for swelling, adding the amino nano-microcrystalline cellulose, stirring for the third time, ultrasonicating for the third time, carrying out a third reaction at 120-125° C. for 2-2.5 hours, adding triethylamine at 75-85° C. for the fourth reaction for 24-25 hours, and carrying out a third post-treatment to obtain dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose; S4: Mix water and dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose for 15-30 minutes to obtain a dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension, spray the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension with a mass concentration of 0.1-0.5wt% on the upper surface of the single-layer prepreg, perform a fourth ultrasonication, dry, and perform a random inspection, and stack the prepregs with uniform distribution of dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose that have passed the random inspection to form N layers, wherein 2≤N≤3000, and the upper surface of each layer of the prepreg sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose is oriented in the same direction, and the uppermost layer is a prepreg not sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose, which is immersed in epoxy resin for 0.5-1h, with a vacuum degree of 0.01-0.1MPa, and cured to obtain a carbon fiber composite material.
[0019] In the present invention, the nano-microcrystalline cellulose is a natural polymer material with high crystallinity extracted from plant fibers, and has the characteristics of extremely high specific surface area, good mechanical strength, excellent biocompatibility and the like.
[0020] In the present invention, the transverse tensile strength is expressed by the interface shear strength.
[0021] In the present invention, dichlorodiphenyl sulfoxide is used to graft nano-microcrystalline cellulose. Unmodified nano-microcrystalline cellulose often has the problem of poor interfacial compatibility when mixed with a hydrophobic polymer matrix due to its high hydrophilicity. Through dichlorodiphenyl sulfoxide grafting, hydrophobic groups can be introduced on the surface of nano-microcrystalline cellulose, which helps to improve the interaction between nano-microcrystalline cellulose and the polymer matrix, thereby improving the mechanical strength and durability of the composite material. In addition, dichlorodiphenyl sulfoxide grafting can reduce the aggregation between nano-microcrystalline cellulose particles and promote its uniform dispersion in the polymer matrix. A better dispersion state means that the strengthening effect of nano-microcrystalline cellulose is more effectively utilized, thereby increasing the overall performance of the composite material. In conjunction with a specific preparation method, specific nano-microcrystalline cellulose is added to the carbon fiber material, which greatly improves the mechanical properties of the original carbon fiber material, so that the prepared carbon fiber composite material has excellent interlaminar shear strength, interface shear strength and bending resistance. Dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose in different directions from the fiber is added between the layers of the unidirectional carbon fiber composite material, so that the overall material has both interlaminar shear strength, transverse tensile strength and bending resistance.
[0022] In the present invention, the random inspection is performed every 100m 2 Prepreg cut 100mm 2 Take a small piece of prepreg and observe whether the BBS-CNCs are evenly distributed on the surface of the prepreg under a scanning electron microscope. If they are evenly distributed, the sample is qualified.
[0023] In the present invention, in the first post-treatment, the second post-treatment and the third post-treatment, the filtration is performed by using a 0.45 μm filter membrane to filter the precipitate.
[0024] In the present invention, the equipment used for spraying is mainly composed of a spray gun and an air compressor.
[0025] According to the present invention, the prepreg is selected from carbon fiber composite material / epoxy resin.
[0026] According to the present invention, in S1, the first stirring condition includes: magnetic stirring, and the first stirring time is 15-20 minutes.
[0027] According to the present invention, in S1, the conditions of the first ultrasound include: the intensity of the first ultrasound is 200-220 J / g, and the time of the first ultrasound is 30-35 min.
[0028] According to the present invention, in S1, the conditions of the first reaction include: the temperature of the first reaction is 85-95° C., and the time of the first reaction is 6-6.5 h.
[0029] According to the present invention, in S1, the conditions of the first post-treatment include: filtering, washing the first precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65°C for 8-8.5h.
[0030] According to the present invention, in S2, the second stirring condition includes: magnetic stirring, and the second stirring time is 15-20 minutes.
[0031] According to the present invention, in S2, the conditions of the second ultrasound include: the intensity of the second ultrasound is 200-220 J / g, and the time of the second ultrasound is 30-35 min.
[0032] According to the present invention, in S2, the conditions of the second reaction include: the temperature of the second reaction is 105-115° C., and the time of the second reaction is 8-8.5 h.
[0033] According to the present invention, in S2, the conditions of the second post-treatment include: filtering, washing the second precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65°C for 8-8.5h.
[0034] According to the present invention, in S3, the swelling conditions include: swelling time of 18-18.5h, swelling temperature of 20-30°C.
[0035] According to the present invention, in S3, the third stirring condition includes: magnetic stirring, and the third stirring time is 15-20 minutes.
[0036] According to the present invention, in S3, the conditions of the third ultrasound include: the intensity of the third ultrasound is 200-250 J / g, and the time of the third ultrasound is 30-35 min.
[0037] According to the present invention, in S3, the conditions of the third post-treatment include: filtering, washing the third precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 hours.
[0038] According to the present invention, in S4, the spraying conditions include: the spray gun air pressure is 0.2-0.25MPa, the distance between the spray gun nozzle and the single-layer prepreg is 10-15 cm, and the volume ratio of the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension to the prepreg is 1:4-5.
[0039] According to the present invention, in S4, the conditions of the fourth ultrasound include: the intensity of the fourth ultrasound is 800-850 J / g, and the time of the fourth ultrasound is 15-20 min.
[0040] In the present invention, the fourth specific ultrasonic condition enables the dichlorodiphenyl sulfoxide in the water suspension to be grafted onto the nano-crystalline cellulose in the same direction.
[0041] According to the present invention, in S4, the drying conditions include: heating at 80-85°C for 20-30 minutes, and then heating at 60-65°C for 12-12.5 hours.
[0042] According to the present invention, the curing conditions include: curing at 20-30° C. for 16-16.5 hours and curing at 80-85° C. for 8-8.5 hours.
[0043] According to the present invention, in S1, the molar ratio of the nano-crystalline cellulose, potassium hydroxide and ethanol is 1:29-32:380-387.
[0044] According to the present invention, in S2, the molar ratio of the hydroxy nano-microcrystalline cellulose, dimethylformamide and acetoxypropyltrimethoxysilane is 1:192-198:6-6.7.
[0045] According to the present invention, in S3, the molar ratio of amino nano-microcrystalline cellulose, maleic anhydride-dichlorodiphenyl sulfoxide, triethylamine and toluene is 1:3.5-3.8:9.6-10:126-131.
[0046] According to the present invention, the carbon fiber composite material has an interface shear strength of 52-70 MPa, a fiber critical length of 220-275 μm, a bending modulus of 20-24 GPa, a bending strength of 280-325 MPa, and an interlaminar shear strength of 28-40 MPa.
[0047] A second aspect of the present invention provides a method for preparing the above-mentioned carbon fiber composite material suitable for strengthening a communication tower, wherein the preparation method comprises: S1: adding potassium hydroxide and nano-microcrystalline cellulose into ethanol, performing a first stirring, a first ultrasound, a first reaction, and a first post-treatment to obtain hydroxy nano-microcrystalline cellulose; S2: adding the hydroxy nano-microcrystalline cellulose to dimethylformamide, performing a second stirring, a second ultrasonication, dropping acetoxypropyltrimethoxysilane, performing a second reaction, and a second post-treatment to obtain amino nano-microcrystalline cellulose; S3: adding maleic anhydride-dichlorodiphenyl sulfoxide to toluene for swelling, adding the amino nano-microcrystalline cellulose, stirring for the third time, ultrasonicating for the third time, carrying out a third reaction at 120-125° C. for 2-2.5 hours, adding triethylamine at 75-85° C. for the fourth reaction for 24-25 hours, and carrying out a third post-treatment to obtain dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose; S4: Mix water and dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose for 15-30 minutes to obtain a dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension, spray the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension with a mass concentration of 0.1-0.5wt% on the upper surface of the prepreg, perform a fourth ultrasonication, dry, and perform a random inspection, and stack the prepregs with uniform distribution of dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose that have passed the random inspection to form N layers, wherein 2≤N≤3000, and the upper surface of each layer of the prepreg sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose is oriented in the same direction, and the uppermost layer is a prepreg not sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose, which is immersed in epoxy resin for 0.5-1h, with a vacuum degree of 0.01-0.1MPa, and cured to obtain a carbon fiber composite material.
[0048] According to the present invention, in S1, the first stirring condition includes: magnetic stirring, and the first stirring time is 15-20 minutes.
[0049] According to the present invention, in S1, the conditions of the first ultrasound include: the intensity of the first ultrasound is 200-220 J / g, and the time of the first ultrasound is 30-35 min.
[0050] According to the present invention, in S1, the conditions of the first reaction include: the temperature of the first reaction is 85-95° C., and the time of the first reaction is 6-6.5 h.
[0051] According to the present invention, in S1, the conditions of the first post-treatment include: filtering, washing the first precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65°C for 8-8.5h.
[0052] According to the present invention, in S2, the second stirring condition includes: magnetic stirring, and the second stirring time is 15-20 minutes.
[0053] According to the present invention, in S2, the conditions of the second ultrasound include: the intensity of the second ultrasound is 200-220 J / g, and the time of the second ultrasound is 30-35 min.
[0054] According to the present invention, in S2, the conditions of the second reaction include: the temperature of the second reaction is 105-115° C., and the time of the second reaction is 8-8.5 h.
[0055] According to the present invention, in S2, the conditions of the second post-treatment include: filtering, washing the second precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65°C for 8-8.5h.
[0056] According to the present invention, in S3, the swelling conditions include: swelling time of 18-18.5h, swelling temperature of 20-30°C.
[0057] According to the present invention, in S3, the third stirring conditions include: magnetic stirring, and the third stirring time is 15-20 minutes.
[0058] According to the present invention, in S3, the conditions of the third ultrasound include: the intensity of the third ultrasound is 200-250 J / g, and the time of the third ultrasound is 30-35 min.
[0059] According to the present invention, in S3, the conditions of the third post-treatment include: filtering, washing the third precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 hours.
[0060] According to the present invention, in S4, the spraying conditions include: the spray gun air pressure is 0.2-0.25MPa, the distance between the spray gun nozzle and the prepreg is 10-15 cm, and the volume ratio of the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension to the prepreg is 1:4-5.
[0061] According to the present invention, in S4, the conditions of the fourth ultrasound include: the intensity of the fourth ultrasound is 800-850 J / g, and the time of the fourth ultrasound is 15-20 min.
[0062] According to the present invention, in S4, the drying conditions include: heating at 80-85°C for 20-30 minutes, and then heating at 60-65°C for 12-12.5 hours.
[0063] In the present invention, in S4, the above-mentioned specific drying method is used to ensure that the water is completely evaporated, so that the dichlorodiphenyl sulfoxide grafted nanocrystalline cellulose (BBS-CNCs) is evenly arranged on the surface of the single-layer prepreg. Since the heating temperature is lower than the prepreg curing temperature of 120°C, the prepreg is still in an uncured state.
[0064] According to the present invention, in S1, the molar ratio of the nano-crystalline cellulose, potassium hydroxide and ethanol is 1:29-32:380-387.
[0065] According to the present invention, in S2, the molar ratio of the hydroxy nano-microcrystalline cellulose, dimethylformamide and acetoxypropyltrimethoxysilane is 1:192-198:6-6.7.
[0066] According to the present invention, in S3, the molar ratio of amino nano-microcrystalline cellulose, maleic anhydride-dichlorodiphenyl sulfoxide, triethylamine and toluene is 1:3.5-3.8:9.6-10:126-131.
[0067] A third aspect of the present invention provides a carbon fiber composite material obtained by the above preparation method.
[0068] A fourth aspect of the present invention provides application of the carbon fiber composite material described in the first aspect or the carbon fiber composite material described in the third aspect in reinforcing a communication tower structure.
[0069] The present invention will be described in detail below through examples.
[0070] Test description: The determination method of interface shear strength is in accordance with GB / T 3354-2014.
[0071] The method for determining the critical fiber length is in accordance with ASTM D3379-75 (2016).
[0072] The determination method of flexural strength shall be in accordance with GB / T 1449-2005.
[0073] The determination method of interlaminar shear strength is in accordance with GB / T 3354-2014.
[0074] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0075] Nanocrystalline cellulose was purchased from Alibaba.
[0076] Maleic anhydride-dichlorodiphenyl sulfoxide (MAH-BBS) was purchased from Aigougou.
[0077] The prepreg has a surface density of 150g / m 2 T300 carbon fiber composite material / epoxy resin.
[0078] Example 1 S1: Add 100g of potassium hydroxide and 10g of nanocrystalline cellulose to 1000mL of 99% ethanol and start stirring. The molar ratio of nanocrystalline cellulose, potassium hydroxide and ethanol is 1:32:387. Stir with a magnetic stirrer for 15 minutes, and then use an ultrasonic processor to ultrasonically treat the solution with 200J / g energy for 30 minutes to obtain a nanocrystalline cellulose aqueous suspension. Pour the above suspension into a flask and reflux in a 90℃ constant temperature oil bath for 6h. Filter the precipitate with a filter membrane with a pore size of 0.45 microns, wash with deionized water and filter the precipitate repeatedly until the pH value is within the range of 7±0.1. Collect the precipitate in a vacuum oven and vacuum dry it at 60℃ for 8h to obtain 11.7g of hydroxyl nanocrystalline cellulose.
[0079] S2: Add 11.7g of hydroxy nano-microcrystalline cellulose to 1000mL of dimethylformamide, stir with a magnetic stirrer for 15 minutes, and then use an ultrasonic processor to ultrasonically treat the solution at 200J / g energy for 30 minutes to obtain a uniform solution. Pour the solution into a flask, and drop 100mL of acetoxypropyltrimethoxysilane. The molar ratio of hydroxy nano-microcrystalline cellulose, dimethylformamide and acetoxypropyltrimethoxysilane is 1:198:6.7, and reflux in a constant temperature oil bath at 110℃ for 8h. After the reaction is completed, filter the precipitate with a filter membrane with a pore size of 0.45 microns, wash with deionized water and filter the precipitate repeatedly until the pH value is within the range of 7±0.1. Collect the precipitate in a vacuum oven and vacuum dry it at 60℃ for 8h to obtain 12.9g of amino nano-microcrystalline cellulose.
[0080] S3: Take 100g of maleic anhydride-dichlorodiphenyl sulfoxide (MAH-BBS) and add it to 1000mL of toluene to swell for 18h. Then weigh 12.9g of amino nano-microcrystalline cellulose and add it to the above solution, stir it with a magnetic stirrer for 15 minutes, and then use an ultrasonic processor to ultrasonically treat the solution with 200J / g energy for 30 minutes to obtain a uniform solution. Pour the solution into a flask and react in a 120℃ constant temperature oil bath for 2h, then lower the temperature to 80℃, gradually add 100mL of triethylamine as a catalyst and condense and reflux for 24h. The molar ratio of amino nano-microcrystalline cellulose, maleic anhydride-dichlorodiphenyl sulfoxide, triethylamine and toluene is 1:3.8:10:131. After the reaction, filter the precipitate with a filter membrane with a pore size of 0.45 microns, wash it with deionized water and filter the precipitate repeatedly until the pH value is within the range of 7±0.1. The precipitate was collected in a vacuum oven and dried at 60° C. in vacuum for 8 h to obtain 12.4 g of dichlorodiphenyl sulfoxide-grafted nanocrystalline cellulose.
[0081] S4: Fill a 2L self-stirring barrel with pure water, pour in 0.3% by weight of dichlorodiphenyl sulfoxide grafted nanocrystalline cellulose (BBS-CNCs) and start stirring. Use a magnetic stirrer to stir for 15 minutes to form a uniform mixed water suspension. Place a single-layer prepreg on a closed operating table. During the spraying process, the air pressure of the spray gun is set to 0.2MPa, the distance between the nozzle and the single-layer prepreg layer is 15cm, and the volume ratio of the sprayed suspended aqueous solution to the prepreg is 1:5. Use an ultrasonic processor to treat the prepreg with a dichlorodiphenyl sulfoxide grafted nanocrystalline cellulose (BBS-CNCs) water suspension attached to the surface for 15 minutes. The ultrasonic intensity is 800J / g, so that the strips of nanocrystalline cellulose in the water suspension are in the same direction. Place a customized heating table under the operating table where the prepreg is placed, heat it at 80°C for 20 minutes to accelerate the complete evaporation of water, and then heat it at 60°C for 12 hours. At every 100m 2 Prepreg cut 100mm 2 Small pieces of prepreg were taken and observed under a scanning electron microscope to see whether the BBS-CNCs were evenly distributed on the surface of the prepreg. The qualified prepregs were stacked, with each layer sprayed facing up, and a layer of ordinary prepreg was laid on the top layer, for a total of 50 layers. The vacuum degree was 0.1MPa and immersed in epoxy resin for 0.5h. The laminate was then taken out and cured at 25°C for 16 hours, and then post-cured at 80°C for 8 hours.
[0082] A carbon fiber composite material A1 was obtained.
[0083] Example 2 The carbon fiber composite material A2 was prepared according to the preparation method of Example 1, except that the mass concentration of the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension in S4 was 0.1%.
[0084] Example 3 The carbon fiber composite material A3 was prepared according to the preparation method of Example 1, except that the mass concentration of the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension in S4 was 0.5%.
[0085] Comparative Example 1 The preparation method of Example 1 is followed, except that in S3, nano-crystalline cellulose grafted with vinyltrimethoxysilane is obtained to prepare the carbon fiber composite material DA1.
[0086] Comparative Example 2 The carbon fiber composite material DA2 was prepared according to the preparation method of Example 1, except that the mass concentration of the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension in S4 was 0.6%.
[0087] Comparative Example 3 Comparative Example 3 is a common carbon fiber board DA3.
[0088] Comparative Example 4 The carbon fiber composite material DA4 was prepared according to the preparation method of Example 1, except that the intensity of the fourth ultrasound in S4 was 500 J / g.
[0089] A1-A3, DA1-DA42 were tested for performance, and the performance parameters are shown in Table 1 below: Table 1 It can be seen from Table 1 that when dichlorodiphenyl sulfoxide grafted nanocrystalline cellulose (BBS-CNCs) is added, the performance of the carbon fiber composite begins to improve. This is because the addition of dichlorodiphenyl sulfoxide grafted nanocrystalline cellulose (BBS-CNCs) leads to deposition on the surface of the prepreg, which not only increases the surface roughness, but also promotes the interface mechanical interlocking between the resin and the carbon fiber matrix, thereby improving the mechanical properties of the carbon fiber composite.
[0090] When the concentration reaches 0.3wt%, the performance is the best, and then it decreases slightly. This is because the surface-covered BBS-CNCs tends to be saturated, resulting in a decrease in roughness. Therefore, the carbon fiber composite material prepared by the aqueous suspension of BBS-CNCs with a mass concentration of 0.1-0.5wt% can achieve the best performance.
[0091] When the concentration is 0.3wt%, the mechanical properties are the best. Compared with the ordinary carbon fiber material DA3, the interface shear strength increases by 41.7% and the critical fiber length decreases by 29.7%, which indicates that the bonding and stress transfer are enhanced. The bending modulus increases by 13.8%, the bending strength increases by 22.6%, and the interlaminar shear strength increases by 59.6%, indicating that the bending performance of the carbon fiber composite material is greatly improved.
[0092] In S4 of Comparative Example 4, an ultrasonic intensity not within the specific range of the present invention is used, and the nano-microcrystalline cellulose in the obtained carbon fiber composite material is not in the same direction, and the performance of the material is inferior to that of the material provided by the present invention.
[0093] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A carbon fiber composite material suitable for strengthening a communication tower, characterized in that: The preparation method of the carbon fiber composite material comprises: S1: adding potassium hydroxide and nano-microcrystalline cellulose into ethanol, performing a first stirring, a first ultrasound, a first reaction, and a first post-treatment to obtain hydroxy nano-microcrystalline cellulose; S2: adding the hydroxy nano-microcrystalline cellulose to dimethylformamide, performing a second stirring, a second ultrasonication, dropping acetoxypropyltrimethoxysilane, performing a second reaction, and a second post-treatment to obtain amino nano-microcrystalline cellulose; S3: adding maleic anhydride-dichlorodiphenyl sulfoxide to toluene for swelling, adding the amino nano-microcrystalline cellulose, stirring for the third time, ultrasonicating for the third time, carrying out a third reaction at 120-125° C. for 2-2.5 hours, adding triethylamine at 75-85° C. for the fourth reaction for 24-25 hours, and carrying out a third post-treatment to obtain dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose; S4: Mix water and dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose for 15-30 minutes to obtain a dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension, spray the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension with a mass concentration of 0.1-0.5wt% on the upper surface of the prepreg, perform a fourth ultrasonication, dry, and perform a random inspection, and stack the prepregs with uniform distribution of dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose that have passed the random inspection to form N layers, wherein 2≤N≤3000, and the upper surface of each layer of the prepreg sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose is oriented in the same direction, and the uppermost layer is a prepreg not sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose, which is immersed in epoxy resin for 0.5-1h, with a vacuum degree of 0.01-0.1MPa, and cured to obtain a carbon fiber composite material.
2. The carbon fiber composite material according to claim 1, characterized in that: In S1, The first stirring conditions include: magnetic stirring, the first stirring time is 15-20min; The conditions of the first ultrasound include: the intensity of the first ultrasound is 200-220 J / g, and the time of the first ultrasound is 30-35 min; The conditions of the first reaction include: the temperature of the first reaction is 85-95° C., and the time of the first reaction is 6-6.5 h; The first post-treatment conditions include: filtering, washing the first precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 hours; In S2, The second stirring conditions include: magnetic stirring, the second stirring time is 15-20min; The conditions of the second ultrasound include: the intensity of the second ultrasound is 200-220 J / g, and the time of the second ultrasound is 30-35 min; The conditions of the second reaction include: the temperature of the second reaction is 105-115° C., and the time of the second reaction is 8-8.5 h; The second post-treatment conditions include: filtering, washing the second precipitate to a pH of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 h; In S3, The swelling conditions include: swelling time of 18-18.5h, swelling temperature of 20-30°C; The third stirring conditions include: magnetic stirring, the third stirring time is 15-20min; The conditions of the third ultrasound include: the intensity of the third ultrasound is 200-250 J / g, and the time of the third ultrasound is 30-35 min; The third post-treatment conditions include: filtering, washing the third precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 hours; In S4, The spraying conditions include: the spray gun air pressure is 0.2-0.25 MPa, the distance between the spray gun nozzle and the prepreg is 10-15 cm, and the volume ratio of the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose water suspension to the prepreg is 1:4-5; The conditions of the fourth ultrasound include: the intensity of the fourth ultrasound is 800-850 J / g, and the time of the fourth ultrasound is 15-20 min; The drying conditions include: heating at 80-85°C for 20-30 minutes, and then heating at 60-65°C for 12-12.5 hours; The curing conditions include: curing at 20-30° C. for 16-16.5 hours and curing at 80-85° C. for 8-8.5 hours.
3. The carbon fiber composite material according to claim 1, characterized in that: In S1, the molar ratio of the nanocrystalline cellulose, potassium hydroxide and ethanol is 1:29-32:380-387; In S2, the molar ratio of the hydroxy nano-microcrystalline cellulose, dimethylformamide and acetoxypropyltrimethoxysilane is 1:192-198:6-6.7; In S3, the molar ratio of amino nano-microcrystalline cellulose, maleic anhydride-dichlorodiphenyl sulfoxide, triethylamine and toluene is 1:3.5-3.8:9.6-10:126-131.
4. The carbon fiber composite material according to claim 1, characterized in that: The carbon fiber composite material has an interface shear strength of 52-70 MPa, a fiber critical length of 220-275 μm, a bending modulus of 20-24 GPa, a bending strength of 280-325 MPa, and an interlaminar shear strength of 28-40 MPa.
5. A method for preparing a carbon fiber composite material suitable for strengthening a communication tower as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises: S1: adding potassium hydroxide and nano-microcrystalline cellulose into ethanol, performing a first stirring, a first ultrasound, a first reaction, and a first post-treatment to obtain hydroxy nano-microcrystalline cellulose; S2: adding the hydroxy nano-microcrystalline cellulose to dimethylformamide, performing a second stirring, a second ultrasonication, dropping acetoxypropyltrimethoxysilane, performing a second reaction, and a second post-treatment to obtain amino nano-microcrystalline cellulose; S3: adding maleic anhydride-dichlorodiphenyl sulfoxide to toluene for swelling, adding the amino nano-microcrystalline cellulose, stirring for the third time, ultrasonicating for the third time, carrying out a third reaction at 120-125° C. for 2-2.5 hours, adding triethylamine at 75-85° C. for the fourth reaction for 24-25 hours, and carrying out a third post-treatment to obtain dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose; S4: Mix water and dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose for 15-30 minutes to obtain a dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension, spray the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose aqueous suspension with a mass concentration of 0.1-0.5wt% on the upper surface of the prepreg, perform a fourth ultrasonication, dry, and perform a random inspection, and stack the prepregs with uniform distribution of dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose that have passed the random inspection to form N layers, wherein 2≤N, and the upper surface of each layer of the prepreg sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose is oriented in the same direction, and the uppermost layer is a prepreg not sprayed with dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose, which is immersed in epoxy resin for 0.5-1h, with a vacuum degree of 0.01-0.1MPa, and cured to obtain a carbon fiber composite material.
6. The preparation method according to claim 5, characterized in that: In S1, The first stirring conditions include: magnetic stirring, the first stirring time is 15-20min; The conditions of the first ultrasound include: the intensity of the first ultrasound is 200-220 J / g, and the time of the first ultrasound is 30-35 min; The conditions of the first reaction include: the temperature of the first reaction is 85-95° C., and the time of the first reaction is 6-6.5 h; The first post-treatment conditions include: filtering, washing the first precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 hours; In S2, The second stirring conditions include: magnetic stirring, the second stirring time is 15-20min; The conditions of the second ultrasound include: the intensity of the second ultrasound is 200-220 J / g, and the time of the second ultrasound is 30-35 min; The conditions of the second reaction include: the temperature of the second reaction is 105-115° C., and the time of the second reaction is 8-8.5 h; The second post-treatment conditions include: filtering, washing the second precipitate to a pH of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 h; In S3, The swelling conditions include: swelling time of 18-18.5h, swelling temperature of 20-30°C; The third stirring conditions include: magnetic stirring, the third stirring time is 15-20min; The conditions of the third ultrasound include: the intensity of the third ultrasound is 200-250 J / g, and the time of the third ultrasound is 30-35 min; The third post-treatment conditions include: filtering, washing the third precipitate to a pH value of 6.9-7.1, and vacuum drying at 60-65° C. for 8-8.5 hours; In S4, The spraying conditions include: the spray gun air pressure is 0.2-0.25 MPa, the distance between the spray gun nozzle and the prepreg is 10-15 cm, and the volume ratio of the dichlorodiphenyl sulfoxide grafted nano-microcrystalline cellulose water suspension to the prepreg is 1:4-5; The conditions of the fourth ultrasound include: the intensity of the fourth ultrasound is 800-850 J / g, and the time of the fourth ultrasound is 15-20 min; The drying conditions include: heating at 80-85° C. for 20-30 min, and then heating at 60-65° C. for 12-12.5 h.
7. The preparation method according to claim 5, characterized in that: In S1, the molar ratio of the nanocrystalline cellulose, potassium hydroxide and ethanol is 1:29-32:380-387; In S2, the molar ratio of the hydroxy nano-microcrystalline cellulose, dimethylformamide and acetoxypropyltrimethoxysilane is 1:192-198:6-6.7; In S3, the molar ratio of amino nano-microcrystalline cellulose, maleic anhydride-dichlorodiphenyl sulfoxide, triethylamine and toluene is 1:3.5-3.8:9.6-10:126-131.
8. A carbon fiber composite material obtained by the preparation method according to any one of claims 5 to 7.
9. Use of the carbon fiber composite material according to any one of claims 1 to 4 or the carbon fiber composite material according to claim 8 in a communication tower.
Citation Information
Patent Citations
Blow molded thermoplastic composition
CN104321383A
Preparation of carbon fiber / epoxy resin prepreg sprayed with aminated carbon nanotubes
CN104558659A
Polyarylene sulfide resin composition
CN105555871A
High-temperature-resistant prepreg for producing carbon fiber composite material, and preparation method therefor
WO2024124837A1